2013
DOI: 10.5152/ttd.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of COPD Exacerbations Managed in Hospital

Abstract: AmAç: Kronik Obstrüktif Akciğer Hastalığı (KOAH) belirgin sağlık ve ekonomik sonuçları olan ve sık görülen bir hastalıktır. Bu çalışmada, hastanemizde KOAH alevlenmesine bağlı yatış gerektiren hastaların maliyet analizi yapılmıştır. Gereç ve Yöntemler: Hastanemiz göğüs servisine, bir yıl boyunca, KOAH alevlenmesi nedeniyle yatışı yapılan 376 hastanın direk maliyet analizi değerlendirilmiştir. BulGulAr: Çalışmaya alınan hastaların 311'i erkek, 65 tanesi kadındır. Hastaların median yatış süresi 8 (ortalama: 9.86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…The mean duration of hospitalization was 8.1 days in this study. In previous studies, the mean duration was 4.5–14.5 days 5–7,19,2224. A longer hospital duration is also associated with increased daily costs due to treatment-resistant, severe cases with many accompanying comorbidities in addition to increased expenditures for hospital stays.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mean duration of hospitalization was 8.1 days in this study. In previous studies, the mean duration was 4.5–14.5 days 5–7,19,2224. A longer hospital duration is also associated with increased daily costs due to treatment-resistant, severe cases with many accompanying comorbidities in addition to increased expenditures for hospital stays.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the total cost of hospitalization due to COPD exacerbations was found to be $808. Previous studies have reported a wide range of cost per hospitalization (between $612 and $9,545) 5–7,1924…”
Section: Discussionmentioning
confidence: 99%
“…An association between age of patients with COPD and increase in healthcare resource utilisation was observed, whereas gender was not considered as an independent predictor of healthcare resource utilisation [42][43][44][45]. Readmission at least twice in the first year of follow-up was observed among 9 % of total patients with COPD studied and was related to increasing age and male gender [46].…”
Section: Impact Of Demographic Characteristicsmentioning
confidence: 93%
“…Considering the studies performed in Turkey, the mean total cost was found to be 1,833.85 TL in a study conducted by Varol et al (15), in which 376 patients with COPD exacerbation who were hospitalized in the Clinic of Thoracic Diseases during 12 months between 2005 and 2006 were evaluated. Also, in their study, the total cost per patient was found to be higher in the group using antibiotics than in the group not using antibiotics.…”
Section: Discussionmentioning
confidence: 99%